Irish America - Byron, Reginald (Oxford University Press, 1999)
"This study, based on interviews with 500 people of Irish ancestry in Albany, New York, aims to discover in what senses and in what degrees the present-day descendants of nineteenth-century Irish immigrants possess distinctive social practices and ways of seeing the world, and raises questions about the social conditions in which ideas of Irishness have been created and recreated."--Jacket
Keywords: Irish Americans -- Ethnic identity.; Irish Americans -- Cultural assimilation.; Américains d'origine irlandaise -- Acculturation.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Irish Americans -- Cultural assimilation; Irish Americans -- Ethnic identity; Ethnische Identität; Assimilation -- Soziologie; Nordamerika; Ieren.; Assimilatie (sociologie); Etnisch bewustzijn.; Iren.